2011
DOI: 10.1007/s00296-011-1880-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and independent predictors of pulmonary arterial hypertension in systemic lupus erythematosus

Abstract: Pulmonary arterial hypertension (PAH) is a devastating complication of systemic lupus erythematosus (SLE). We aim to estimate the putative predictors contributing to early identification of PAH, thus improve appropriate medical intervention and a better prognosis. A retrospective case-control study was conducted. Forty-one SLE patients with PAH and 106 SLE patients without PAH were enrolled. Demographic variables, clinical features, and laboratory data were compared between the two groups. Univariate and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 26 publications
6
71
1
2
Order By: Relevance
“…Parambil et al (23) reported that three patients developed AE to die, among 18 patients with SS-IP (16.6%). And Lian et al (24) reviewed 4038 SLE patients and described that 9.4% of SLE patients associated IP and 1.1% of SLE-IP developed AE. This shows that AE may develop in also SS-IP or SLE-IP.…”
Section: Discussionmentioning
confidence: 99%
“…Parambil et al (23) reported that three patients developed AE to die, among 18 patients with SS-IP (16.6%). And Lian et al (24) reviewed 4038 SLE patients and described that 9.4% of SLE patients associated IP and 1.1% of SLE-IP developed AE. This shows that AE may develop in also SS-IP or SLE-IP.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of aPL antibodies was noted in all patients with SLE and PAH (15/15) as compared to only 5/15 in patients with SLE without PAH. Mutiple studies have noted the presence of positive anticardiolipin antibodies (aCL) has a significant association with PAH and SLE patients (18)(19)(20)(21). Similarly Houman et al found out that the frequency of PAH in SLE was higher in patients with antibodies against B2Glycoprotein I (B2GPI) than those without these antibodies (22).…”
Section: Pulmonary Hypertension Associated With Connective Tissue Dismentioning
confidence: 94%
“…(Table-I Anti-Phospholipid Syndrome (APS) is a hype coagulable state, correlation between pulmonary embolism were significantly high in SLE patients who were anti-Cardiolipin antibodies, lupus anticoagulant (LAC) and Beta2 glycoprotein 1 (B2GP1) anti -bodies positive (Table-III), with significant odds ratio (OR), 95% confidence interval (CI), and p-value <0.0001. 4 and others were included. Lung involvement had been investigated in SLE patients previously using various techniques.…”
Section: Resultsmentioning
confidence: 99%
“…With HRCT, delineation of the lung parenchyma down to the secondary lobule level is possible. 4 The purpose of this study was to evaluate HRCT chest, individual and combination of various patterns of findings in SLE patients.…”
Section: Introductionmentioning
confidence: 99%